Follicular dynamics and in vitro embryio production after repeated superovulation with FSH_P in Simmental heifers - Getz, Iva; Samardžija, Mirjana; Karadjole, Ivo; Makek, Zdenko Bedrica, Ljiljana; Karadjole, Tugomir Gračner, Damijan (2005)
Ultrasound transvaginal ovum pick-up was perofmed in 6 Simmental heifers aged between 14 and 18 month. The results show that the repeated FSH stimulation prior to ovum pick-up does not affect the follicular dynamic and developmental competence of bovine oocytes in Simmental heifers.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG